Adjusting EFL Learners’ Attitudes towards Writing - Tebib , Djalal; Labed, Nacif (Journal of Human Sciences, 2023)
Foreign language writing is unquestionably an intricate process, and many EFL learners may consequently develop an aversion to the writing skill. This paper aims at positively changing EFL learners’ attitudes towards the craft of writing through a series of innovative writing activities designed by the researcher. To attain this objective, a group of EFL students have received a six-month writing training in a writing centre at the American Corner, University of Constantine. The obtained results showed that exposing students to certain type of creative writing activities and tasks can successfully change the way they perceive writing, and thus began to improve their skills accordingly.